Ecological assessment of aquatic resources : (Society of Environmental Toxicology and Chemistry (SETAC), 2000)
Ecological assessments have been conducted for decades; however, many who use ecological assessments fail to carry them out effectively. With a goal of introducing science into the decision-making process, 60 individuals representing government, industry, academia, and nongovernmental organizations from different countries participated in a SETAC Pellston Workshop to address the relationship between ecological assessment and ecological risk assessment and their roles in aquatic resources. A result of that workshop, this book presents guidelines for effectively conducting and communicating ecological assessments. Through successful integration of economic, social, and behavioral perspectives and approaches, ecological assessments can ultimately produce sound decisions to protect and manage our aquatic resources.